Fondamenti e implicazioni teologiche del sacramento della riconciliazione - Ladaria, Luis F. 1944- (2020)
L’articolo commenta i fondamenti e le implicazioni teologiche del Sacramento della Riconciliazione, in particolare mettendo in luce il valore della misericordia. Particolare attenzione viene data alle diverse denominazioni di tale Sacramento lungo diverse epoche storiche e nei documenti della Chiesa, al ruolo del confessore che da queste consegue e all’inviolabilità del sigillo sacramentale all’interno della misericordiosa accoglienza al penitente.
Foundations and Theological Implications of the Sacrament of Reconciliation. The article comments on the foundations and theological implications of the Sacrament of Reconciliation, in particular highlighting the value of mercy. Particular attention is given to the different denominations of this Sacrament throughout different historical periods and in the documents of the Church, to the role of the confessor that follows from them and to the inviolability of the sacramental seal within the merciful welcome to the penitent.
Keywords: Barmherzigkeit; Beichtgeheimnis; Gewissenserforschung